Intersectional oppression of women in Season of Migration to the North: A Comparative analysis of Sudanese and British female characters - Zahroh, Adiba Qonita; Sari, Nabila Intan (NOTION: Journal of Linguistics, Literature, and Culture, 2025)
Women’s oppression remains a critical global issue, as reflected in Tayeb Saleh’s “Season of Migration to the North”. This study examines the intersecting dimensions of oppression faced by the novel’s female characters, employing Sean Ruth’s (1988) theory of oppression—physical, psychological, internalized, and economic—and Kimberlé Crenshaw’s (1989) theory of intersectionality (the idea that overlapping identities such as gender, race, and culture create distinct forms of disadvantage). It also attends to “double colonization,” namely women’s simultaneous subjection to colonial power and to local patriarchal control. The purpose of this research is to analyze how the novel portrays systemic oppression through the experiences of both black Sudanese and white British women by focusing on how intersecting identities amplify their marginalization. A qualitative descriptive method was applied through close reading and analysis of key passages to identify evidence of oppression and its broader societal implications. The results reveal that black Sudanese women, such as Hosna Bint Mahmoud, endure compounded oppression driven by cultural norms, religious interpretations, and economic dependency. In contrast, British women experience gendered violence and manipulation despite their racial privilege within colonial hierarchies. The novel’s distinctive contribution to postcolonial feminist discourse lies in its exposure of a paradox: acts framed as resistance to colonial dominance can reproduce patriarchal harm; and this shows that power circulates across multiple domains rather than along a single axis. In conclusion, this study highlights how “Season of Migration to the North” critiques patriarchal and colonial dominance by offering a comprehensive understanding of how overlapping systems of power shape women’s experiences in postcolonial contexts.